Current recommended management of common STIs in primary care. Issue 11 (5th June 2014) - Gupta, Nadi; Kinghorn, George
Abstract Without effective treatment sexually transmitted infections can lead to serious complications. Our Drug review describes the current treatment options for the most commonly encountered STIs in general practice, followed by sources of further information.